Azerbaijan - Country Economic Memorandum : A New Silk Road - Export-led Diversification - World Bank (World Bank, 2012)
Azerbaijan's oil and gas boom presents a rare opportunity to accelerate improvements in the quality of life of all its citizens. Its per capita income is $5,100 in 2008, up nearly 400 percent from 2004 in current USD terms; it could potentially exceed $6,500 by 2013 and higher beyond that. Consequently, poverty is likely to continue to fall, especially in the rural areas, and the entire population of nearly nine million can expect to benefit significantly from expanded access to better quality education and health services as well as more targeted social assistance. Most of this income growth is expected to come from non-oil output and exports, especially agriculture and light manufacturing, though high levels of oil revenues and public spending will continue to stimulate significant growth of construction and various services sectors. Fiscal revenues from oil and gas are expected to be $198 billion in net present value terms through 2024 (based on the oil production profile of June 2008). This report outlines changes in policies and institutions that will be needed to realize this vision.